Factors affecting direction and strength of patient preferences for treatment of molar teeth with nonvital pulps. (10th December 2014) - Vernazza, C. R.; Steele, J. G.; Whitworth, J. M.; Wildman, J. R.; Donaldson, C.
Abstract Aim To elicit the factors affecting willingness to pay (WTP) values for the preferred options of participants for dealing with a molar tooth with a nonvital pulp, a common but difficult problem. Methodology A total of 503 patients were recruited from dental practices in the North East of England and interviewed. Their preferred treatment option for a molar tooth with a nonvital pulp (endodontics, extraction and various prosthetic restorative options) and WTP for this preferred option were elicited. Factors affecting preferred option and WTP were analysed using econometric modelling. Results Overall, 53% of the sample wished to save the tooth with a mean WTP of £373. The variance in WTP was high. Of those opting for extraction, the majority chose to leave a gap or have an implant. The preferred option was influenced by previous treatment experience. WTP was only influenced by having a low income. Conclusions The high level of variance in WTP and its relatively unpredictable nature pose difficult questions for policy makers trying to ensure the delivery of an equitable service. For dentists, it is important not to make assumptions about patient preference and strength of preference when making decisions. Ideally, WTP values should be considered alongside effectiveness data, and those on costs, in policy making.